Problematika Kepastian Hukum Itsbat Nikah Atas Perkawinan di Bawah Batas Usia - Bustomi, Muhammad Nizar; Sulistyarini, Rachmi; Hidayat, Fitri (RechtJiva, 2026)
This study is motivated by the ambiguity surrounding the phrase “impediment to marriage” in Article 7(3)(e) of the Compilation of Islamic Law (KHI). This phenomenon arises due to several Religious Court Decisions that granted requests for itsbat nikah (marriage validation) for couples under the minimum age without going through the marriage dispensation mechanism as mandated by Law No. 1 of 1974. The objective of this study is to analyze the criteria of the phrase “marriage impediment” in the aforementioned article and to examine whether the judges’ rulings granting such requests have met the principle of legal certainty. The research method employed is normative legal analysis using a statutory approach and a case approach. Legal analysis was conducted using grammatical, systematic, and extensive interpretation techniques. The results of the study indicate that the criteria for the phrase “marriage impediment” in Article 7(3)(e) of the KHI encompass four criteria that must be applied cumulatively, namely: Absolute Impediments, Religious or Belief-Based Impediments, Binding Impediments, and Conditional Impediments. The Religious Court’s decision granting itsbat nikah for a marriage below the age limit was found to lack legal certainty due to the presence of a “conditional impediment” in the form of a violation of the minimum age limit. Furthermore, this practice contradicts the guidelines of SEMA No. 7 of 2012, which stipulate that there must be no violation of the law in the marriage to be validated.